Magnetic resonance imaging in boys with severe hemophilia A: Serial and end‐of‐study findings from the Canadian Hemophilia Primary Prophylaxis Study. Issue 7 (16th October 2021) - Stimec, Jennifer; Dover, Saunya; Pullenayegum, Eleanor; Blanchette, Victor S.; Doria, Andrea S.; Feldman, Brian M.; Carcao, Manuel; Rivard, Georges E.; Israels, Sara J.; Chan, Anthony K.; Steele, MacGregor; Cloutier, Stephanie; et al.
Abstract: Background: This study examined the structural outcomes for joints of boys with severe hemophilia A receiving frequency/dose‐escalated primary prophylaxis using magnetic resonance imaging (MRI), and the importance of interval MRI changes. Methods: Forty‐six subjects (27 with interval studies) were evaluated by radiographs (X‐rays) and mid‐ and end‐of‐study MRIs (using the International Prophylaxis Study Group scale), as part of the Canadian Hemophilia Prophylaxis Study. The primary outcome was the presence of MRI osteochondral findings. Results: The median (range) time on study at the end‐of‐study MRI examination was 9.6 (4.8–16.0) years, during which 18 of 46 subjects (39%) had osteochondral changes in at least one joint. An interval change in MRI score of at least 1 point was observed in 44% of joints (43 ankles, 21 elbows, 4 knees); at least one joint showed this change in all 27 subjects. Self‐reported interval hemarthrosis was associated with a higher likelihood of interval osteochondral change (odds ratio [OR], 1.49; 95% confidence interval [CI] = 1.08–2.06). Presence of synovial hypertrophy or hemosiderin on interval MRIs was associated with an OR of 4.71 (95% CI, 1.92–11.57) and 5.25 (95% CI, 2.05–13.40) of later osteochondral changes on MRI. Discussion: MRI changes were seen in 39% of subjects. Interval index joint bleeding was associated with an increased risk of later MRI changes, and earlier soft‐tissue changes were associated with subsequent osteochondral changes. Abstract : Horner's syndrome (HS) occurs when the sympathetic nerve pathway is disrupted. This case report describes a cat with acromelanism that developed unilateral facial hypopigmentation concurrently with HS after an oesophagostomy tube was placed. Both the hypopigmentation and HS resolved completely following removal of the oesophagostomy tube.